Greek meets Turkish at the western edge of Asia: Case markers and complementizers under language contact - Bağrıaçık, Metin; Göksel, Ash; Ralli, Angela (Investigationes Linguisticae, 2019)
We investigate case and clausal complementation systems in Cunda Turkish spoken in Western Turkey by refugees relocated from Crete (Greece) in and after 1923. Unlike Standard Turkish, Cunda Turkish exhibits unpredictable dative–locative and dative–accusative shifts. We claim these shifts are due to interference of the heritage language, Cretan Greek. Cunda Turkish subordination patterns also differ from those of the standard variety. Contrary to the case in Standard Turkish, nominalizing suffixes are employed only when selecting (matrix) predicates are non-factive veridical ones. Non-veridical predicates, on the other hand, select subordinate clauses that are in optative mood, a preexisting Turkish pattern which has nevertheless been reinforced by Cretan Greek impact. Finally, clauses that are complements to factive predicates are indicative clauses headed by an optional complementizer, a pattern which is extended to these clauses from factive adverbial clauses.